An optimized flow cytometry panel for classifying macrophage polarization - Liu, Liyuan; Stokes, John V.; Tan, Wei; Pruett, Stephen B. (Journal of immunological methods, 2022)
Macrophages are scavenger cells and a fundamental part of innate and adaptive immune responses, and they are important in wound repair and tissue remodeling. The functions of macrophages include engulfing and killing invading pathogens, processing and presenting antigens, initiation of inflammation, secreting cytokines and other inflammatory mediators, and participating in the maintenance and repair of tissues. Based on functional differences and surface and intracellular marker expression, macrophages can be generally divided into either M1 (inflammatory) or M2 (wound healing); the M2 type can be further divided into M2a, M2b, M2c, and M2d. However, due to the time, effort, and cost of establishing a panel of markers that could thoroughly assess polarization, the characterization of types and subtypes is usually done using three markers or fewer. This can lead to problems, because the expression of some of the most widely used polarization markers can be altered by commonly used inflammatory or immunological stimuli. We have developed and optimized an eleven-color polychromatic flow cytometric assay for macrophage subtype identification that prevents mischaracterization due to stimulus-induced changes in individual markers by using partially redundant markers for which at least one is not substantially affected by a commonly used inflammatory stimulus (LPS). We polarized 3 × 105 RAW 264.7 cells, a mouse macrophage cell line, with IFN-γ (± LPS), IL-4 or IL-10 to derive M1, M2a, or M2c macrophage subtypes, respectively. The TNF-α concentration in cell supernatants was tested by ELISA to verify polarization. Then polarized cells were labeled with the following antibodies and assessed by flow cytometry to identify marker expression: F4/80, Arginase 1, TLR4, CD86, VEGF, CD14, CD206, MHC Class II, and TNF-α (surface and internal). Here we have identified clear distinctions between macrophage subtypes using these markers, and we anticipate that this panel will help disclose more details of the macrophage's role in the immune response and will save investigators the time and cost usually required to identify appropriate antibodies that do not interfere with each other or lead to difficult color compensation issues. [Display omitted]